Komparasi perspektif hukum pernikahan dini ditinjau dari ‎hukum perdata dan hukum Islam - Nurfaizah, Hartika (Maliki Interdisciplinary Journal, 2023)
Marriage according to UU No. 1 Tahun 1974 is a bond between a man and a woman as husband and wife with the aim of forming a happy family and provision based on the Godhead of the Almighty. In the legislation has also been mentioned that the marriage age limit is at the age of 19 years. But the reality in Indonesia is that the number of underage marriages still occurs a lot. The purpose of this study is to conduct an analysis of early marriage based on the basis of civil law and Islamic law. The research was conducted in normative juridical manner, where researchers conducted case analysis based on primary legal sources and secondary legal sources. The results showed that under the legislation under the legislation under the marriage of minors is not allowed unless under certain circumstances can apply for dispensation to carry out underage marriage. While based on Islamic law there are no clear rules regarding the age limit for performing marriage, but there are some provisions such as physical, mental and material readiness that must be met in order to carry out. Early marriage is not recommended because it can have a negative impact both in terms of physical, mental, and social children.